CULTURAL ASPECTS IN LITERARY WORK AS A REFLECTION OF HUMAN LIVES - Apriyanti, Chusna; Irawati, Iisrohli (MAGISTRA, 2015)
This paper is aimed to explain the cultural aspects in literary works through three different kinds of literature (Indonesian literature, British literature, and American literature). The researcher uses descriptive qualitative research design. The data are collected by reading activities. The result shows that the aspects of human lives can be seen in cultural aspects of literary works. The first is social relation that was found in the novel Weton Bukan Salah Hari by Dianing Widya Yudhistira, Oliver Twist by Charles Dickens, and a short story Superman and Me by Sherman Alexie. The psychological aspect was found in the novel Nayla by Djenar Maesa Ayu, Oliver Twist by Charles Dickens, and a short story A Rose for Emily by William Faulkner. The own-individual habit was found in Chinese literary work entitled Memoirs of a Geisha by Arthur Golden, The Art of Virtue by Benjamin Franklin, and Superman and Me by Sherman Alexie. The religious aspect was found in the novel Ayat-Ayat Cinta by Habiburrahman El Shirazy, Oliver Twist by Charles Dickens, and (Deliverance) from Another Sore Fit by Anne Bradstreet. The value aspect was found in the novel Laskar Pelangi and Sang Pemimpi by Andrea Hirata (education), Harimau! Harimau! by Mochtar Lubis (moral), Kambing Jantan by Raditya Dika (entertainment), and Civil Disobedience and Resistance to Civil Government by Henry David Thoreau (critic). Keywords: culture, literary work, cultural aspects, human lives